The Analysis of Science Process Skills Using Virtual Chemistry Experiments (OLabs) on Reaction Rate Materials - Reynata Firoos; Yenni Kurniawati (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2025)
This research aimed at analyzing students' science process skills in experimental and control groups, and knowing the effect of learning media using virtual chemistry experiments online labs (OLabs) to students' science process skills. This research was conducted at XI IPA grade of State Senior High School 1 Keritang 2021/2022 academic year with factors influencing Reaction Rate material. It was a mixed method research with explanatory design. The instruments of this research were essay test for knowing student science process skills and interview for knowing students’ responses and strengthen the results of the data obtained. The findings of this research showed that the average posttest results of science process skills were 74.84 for the experiment group and 64,242 for the control group. Based on the results of hypothesis test using SPSS obtained that Sig. 2 tailed = 0.000 < 0.05, it means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. The indicators of science process skills between experimental and control groups which has the highest difference was the grouping indicator (22.29). Therefore, it could be concluded that there was the different skills of student science process using and not using chemistry experiments Online (OLabs).